Navigating Institutional Culture in Ensuring the Ethical Use of Data in Support of Student Success and Institutional Effectiveness. Issue 183 (26th May 2020) - Cubarrubia, Archie; Le, Michael
Abstract: In this chapter, we explore the contexts within which institutional researchers must try to ensure the ethical use of data. We also identify challenges institutional research professionals can face when navigating college culture while trying to ensure the ethical use of data. Finally, we identify potential solutions for improving institutional data culture.